Metatarsals of Blue Bull (Boselaphus tragocamelus): A Gross Morphological and Morphometrical Study - Bharti, Sanjay Kumar (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on the metatarsals of six adult blue bull of either sex. The macerated samples were soaked in 4% hydrogen peroxide, followed by the sun-drying for 5 days. In the present study, the metatarsus of the blue bull consisted of two metatarsal bones. The large metatarsal bone consisted of fused III and IV metatarsals. The small II metatarsal was also present. These were cord-like bones and did not reach the distal extremity. The metatarsal II was smaller and was present on the palmo-lateral aspect of the large metatarsal. Two fully developed digits (III) and (IV) were reported in each hind limb of the blue bull.